Study the efficacy of intralesional formic acid-80% in verruca vulgaris - Tippanawar, Shantiprasad A.; Kadam, Manish N.; Phatale, Sangita R.; Kadam, Pranita M. (International Journal of Advances in Medicine, 2017)
Background: Warts have been recognized for thousands of years. A wart an epidermal outgrowth develops due to infection with human papilloma virus (HPV) belongs to the papova viridae group. Various treatment modalities have been tried for warts but none are uniformly effective. The present experimental study with formic acid 80% was undertaken. The objective was to study the verruca vulgaris in relation to age, sex and site and efficacy of intraregional formic acid 80% in verruca vulgaris. Methods: Patients were treated with formic acid - 80% intralesionally on every alternate day till lesions become flat. But the number of application was restricted to ten, after which the treatment was considered as a failure. Then follow up every monthly. Failure was considered if there was recurrence of any lesion and if lesions did not respond to intraregional formic acid. Results: In the present study, out of 67 patients of verruca vulgaris, 64 patients showed complete disappearances of verruca vulgaris before the period of 10 application of formic acid 80%. The overall success rate of treatment of verruca vulgaris with 80% formic acid is 82%. Conclusions: The overall success rate of treatment of verruca vulgaris with formic acid was 82%. Thus the formic acid-80% is effective in the treatment of verruca vagaries.